Identification of métiers in a multi-gear, multi-species fishery - Pedro Leitão; Margarida Castro; Aida Campos (PLoS ONE, 2026)
Accurate, gear-specific data is essential for fisheries management to quantify fishing pressure and ecosystem impacts, particularly in multi-gear fleets. In this study, we used electronic logbooks and sales notes from 2014 to 2023 to analyze the Portuguese multi-gear coastal fleet, obtaining information at a haul level. The objective was to identify and validate métiers down to level 6 according to the European Commission’s definition (a combination of gear specifications, target species, fishing area, and season). This fleet comprises approximately 500 vessels using various types of traps, nets, and longlines to catch around 200 species of fish and invertebrates. We identified 28 métiers across six main gear types. The most representative métier is the octopus ( Octopus vulgaris ) trap fishery, followed by the European hake ( Merluccius merluccius ) gillnet and the black scabbardfish ( Aphanopus carbo ) longline fisheries. A strong association was found between most métiers and variables such as fishing season, fishing area, depth, and sediment type. Traps and nets were mostly used in the northwest area, in mixed sediments or sand, whereas longlines were mostly operated in the central west area, in steeper slopes on sandy and rocky bottoms. The study highlights the complexity of quantifying gear-specific fishing effort in multi-gear fisheries, where technical interactions occur, and competitive relationships exist between different fishing fleets and gears that exploit the same fish stocks.